1, 4‐Dioxane‐degrading consortia can be enriched from uncontaminated soils: prevalence of Mycobacterium and soluble di‐iron monooxygenase genes. Issue 1 (6th October 2017) - He, Ya; Mathieu, Jacques; da Silva, Marcio L.B.; Li, Mengyan; Alvarez, Pedro J.J.
Summary: Two bacterial consortia were enriched from uncontaminated soil by virtue of their ability to grow on 1, 4‐dioxane (dioxane) as a sole carbon and energy source. Their specific dioxane degradation rates at 30°C, pH = 7 (i.e. 5.7 to 7.1 g‐dioxane per g‐protein per day) were comparable to those of two dioxane‐metabolizing archetypes: Pseudonocardia dioxanivorans CB1190 and Mycobacterium dioxanotrophicus PH‐06. Based on 16S rRNA sequencing, Mycobacterium was the dominant genus. Acetylene inhibition tests suggest that dioxane degradation was mediated by monooxygenases. However, qPCR analyses targeting the tetrahydrofuran/dioxane monooxygenase gene ( thmA/dxmA ) (which is, to date, the only sequenced dioxane monooxygenase gene) were negative, indicating that other (as yet unknown) catabolic gene(s) were responsible. DNA sequence analyses also showed threefold to sevenfold enrichment of group 5 and group 6 soluble di‐iron monooxygenase (SDIMO) genes relative to the original soil samples. Whereas biodegradation of trace levels of dioxane is a common challenge at contaminated sites, both consortia degraded dioxane at low initial concentrations (300 μg l −1 ) below detectable levels (5 μg l −1 ) in bioaugmented microcosms prepared with impacted groundwater. Overall, this work shows that dioxane‐degrading bacteria (and the associated natural attenuation potential) exist even in some uncontaminated soils, and may be enriched to broaden bioaugmentation options for sites experiencing insufficient dioxane catabolic capacity. Abstract : Two bacterial consortia were enriched from uncontaminated soil by virtue of their ability to grow on 1, 4‐dioxane (dioxane) as a sole carbon and energy source. Based on 16S rRNA sequencing, Mycobacterium was the dominant genus. DNA sequence analyses showed 3‐ to 7‐fold enrichment of group‐5 and group‐6 soluble diiron monooxygenase genes relative to the original soil samples.